2010
DOI: 10.1159/000320543
|View full text |Cite
|
Sign up to set email alerts
|

Cell Swelling-induced Insulin Secretion from INS-1E Cells is Inhibited by Extracellular Ca<sup>2+</sup> and is Tetanus Toxin Resistant

Abstract: Cell swelling-induced insulin secretion represents an alternative pathway of stimulation of insulin secretion. INS-1E rat tumor beta cells do not release insulin in response to cell swelling in presence of Ca2+ despite a good response to glucose challenge and appropriate increase in cell volume. Surprisingly, perifusion with Ca2+-depleted medium showed distinct secretory response of INS-1E cells to hypotonicity. Objective of this study was further characterization of the role of Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Recently, it has been reported that Nifedipine prevented induced apoptosis in endothelial cells and smooth muscle cells [40,41]. The l -type Ca 2+ channel has been reportedly expressed in INS-1 β-cells [42,43], and β-cells were also thought to be sensitive to calcium channel blockers [44], and Jeffrey et al . demonstrated that blocking Ca 2+ influx with nifedipine could abolish the palmitate-induced ER stress [45].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that Nifedipine prevented induced apoptosis in endothelial cells and smooth muscle cells [40,41]. The l -type Ca 2+ channel has been reportedly expressed in INS-1 β-cells [42,43], and β-cells were also thought to be sensitive to calcium channel blockers [44], and Jeffrey et al . demonstrated that blocking Ca 2+ influx with nifedipine could abolish the palmitate-induced ER stress [45].…”
Section: Discussionmentioning
confidence: 99%
“…These results are indeed expected when considering the proposal that Ca 2+ -independent pathways contribute minimally to GSIS 78 . However, they also suggest that the modulatory effect that KCC2 inhibition has on insulin secretion does not involve potential secretory mechanisms, which are not dependent on Ca 2+ entry such as hypotonicity-induced cell swelling 79 or increased cAMP 80 . Although it has been reported that β-cell membrane potential does not change in response to 1.1 mM, 3.3 mM or 5.5 mM glucose 81 , a detailed analysis as that performed recently 23 will be needed to elucidate the mechanisms whereby KCC2 inhibition promotes Ca 2+ entry.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of L-type and/or P/Q-type calcium channels also enabled distinct response to hypotonic medium of INS-1E cells in Ca 2+ containing medium [86]. At these conditions tetanus toxin inhibited hypotonicity -induced insulin secretion from INS-1 cells but not from INS-1E cells [86]. Interesting enough, Straub et al [50] found two different exocytotic mechanisms operating in hyposmotic shock in GH4Cl cells in the presence and absence of Ca 2+ in the medium.…”
Section: Ins-1 and Ins-1e Cellsmentioning
confidence: 95%
“…They found that desorption of cholesterol leads to the disturbance of a basic exocytotic mechanism partly due to migration of SNAP-25, and concluded that insulin secretion is highly sensitive to changes in plasma membrane cholesterol. In our recent experiments comparison of two insulin secreting tumor cell lines revealed surprising differences: while INS-1 line responded to both glucose and hyposmotic stimulation, INS-1E was unable to respond to osmotic stimulus while response to glucose was regular [56,86]. Cellular content of cholesterol of INS-1E was much higher than that of INS-1 [87].…”
Section: N-ethylmaleimide-sensitive-factor (Nsf) and Soluble Nsf-attamentioning
confidence: 99%
See 1 more Smart Citation